Amino Borate-Functionalized Reduced Graphene Oxide Further Functionalized with Copper Phthalocyanine Nanotubes for Reducing Friction and Wear - Verma D.K.; Kuntail J.; Kumar B.; Singh A.K.; Shukla N.; Kavita; Sinha I.; Rastogi R.B. (My University, 2025)
Covalent functionalization of graphene oxide (GO) was performed by 2-aminoethyl diphenyl borate (ADB) to overcome the demerits of plain GO/reduced GO (rGO) during lubrication such as the agglomeration and restacking of nanosheets, poor dispersibility in the base lube, poor adhesion to the steel surface, inadequate friction and wear-reducing characteristics, and last abysmal load-carrying ability. ADB was deliberately chosen to outreach the benefits of the enhanced lubrication by in situ formed boron nitride during tribological testing due to boron-nitrogen synergy. Nucleophilic attack of the -NH2 group of ADB opened epoxide rings of GO, forming -NH-C-C-OH and simultaneously reducing GO to rGO. The product, therefore, is represented as ADB-rGO. For the betterment of lubricity, further noncovalent functionalization was also considered using triboactive phthalocyanine (Pc) or copper(II) phthalocyanine (CuPc). Based on the results of molecular dynamics and tribological tests in paraffin oil (PO), CuPc was preferred over Pc. Configurations of the adsorbate CuPc on the surface reveal that CuPc tends to fold/unfold upon adsorption. Thus, the CuPc nanotubes (NTs) were used for the noncovalent functionalization of ADB-rGO. The techniques FTIR, p-XRD, SEM/HR-SEM, TEM/HR-TEM, EDX, and XPS were applied to characterize the additives. The tribological activity of different additives evaluated on a four-ball tester based on ASTM D4172 and ASTM D5183 tests reveals the order for antiwear/antifriction efficiencies and reduction in wear rates as CuPc-(ADB-rGO) > CuPc NTs > Pc > ADB-rGO > GO > PO. Thus, CuPc-(ADB-rGO) overpowered the demerits of GO. The morphology of the surface lubricated with GO, ADB-rGO, was studied using SEM and AFM (contact mode). EDX analysis of the steel surface in the presence of CuPc-(ADB-rGO) divulges the additional elements boron, nitrogen, and copper in the in situ formed tribofilm, highlighting their active role in improving the tribological activity. XPS studies of the tribofilm show boron nitride, boron oxide, iron oxides, cupric oxide, and graphitic compounds. The synergic performance of layered structures rGO, CuPc, and in situ formed boron nitride validated the spectacular tribological performance of CuPc-(ADB-rGO). © 2020 American Chemical Society.